Aplikasi Pembelajaran Pendidikan Agama Islam dalam Projek Penguatan Profil Pelajar Pancasila - Umni Afifah (Proceedings Series on Social Sciences & Humanities, 2023)
The Pancasila Student Profile Strengthening Project is a program in the independent curriculum as an effort to improve the quality of education through character education. In accordance with the implementation of the this project, there are links to subjects, one of which is Islamic Religious Education. Islamic Religious Education as one of the important subjects and has a large role in the implementation of this project because one of the competencies of this project is faith, piety to God Almighty, and noble character, this is closely related to the subject of Islamic Religious Education. So that this paper will discuss in depth the application of Islamic Religious Education learning in the Pancasila Student Profile Strengthening Project. This research is a field research with data collection techniques being observation and interviews. The analysis of the data of this study is presented descriptively from the data that has been collected. The results of this study show that the application of Islamic Religious Education learning in the Pancasila Student Profile Strengthening Project is not only in the dimensions of faith, piety to God Almighty, and has a noble character but contains all six dimensions of the Pancasila profile. This is because this project can be achieved optimally because it is preceded by the learning process of Islamic Religious Education which is carried out systematically and interactively.